Observations on the behavior of Schroederichthys chilensis (Carcharhiniformes, Scyliorhinidae) - Flores, Daniel (2014)
Schroederichthys chilensis, the redspotted catshark or chilean catshark, is an endemic species to Peruvian and Chilean waters. Observations on its behavior in the National Reserve System of Guano Islands, Islets, and Capes – Punta San Juan and Paracas National Reserve reveal that it curls when threatened. This hypothesized survival strategy has not been previously documented in this species and we recommend further studies to elucidate this behavior.